1985
DOI: 10.1111/j.1365-2125.1985.tb05041.x
|View full text |Cite
|
Sign up to set email alerts
|

Single dose pharmacokinetics and pharmacodynamics of oral loprazolam in the elderly.

Abstract: 1 The pharmacokinetics of the benzodiazepine hypnotic, loprazolam (1.0 mg orally), and the pharmacodynamic response to single oral doses (0.5 mg and 1.0 mg) have been compared in young and elderly healthy volunteers.2 No difference between the groups in peak plasma concentration (Cma,) or in the time to peak (tmax) was found, but the elimination half-life t½,2z and area under the plasma concentration-time curve (AUC) were significantly greater in the elderly group. 3 The immediate effects of loprazolam on al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(12 citation statements)
references
References 31 publications
(22 reference statements)
1
11
0
Order By: Relevance
“…1977b, Triggs et af. 1975: Moreover, this result is in accordance with the results of Swift et al (1985), in both young and elderly healthy volunteers, following administration in the morning after an overnight fast. There was considerable inter-subject variability between the times to peak concentration, which is not uncommon with benzodiazepines.…”
Section: Discussionsupporting
confidence: 86%
“…1977b, Triggs et af. 1975: Moreover, this result is in accordance with the results of Swift et al (1985), in both young and elderly healthy volunteers, following administration in the morning after an overnight fast. There was considerable inter-subject variability between the times to peak concentration, which is not uncommon with benzodiazepines.…”
Section: Discussionsupporting
confidence: 86%
“…In a series of experimental trials, Swift et al have found that benzodiazepines impair reaction time and postural sway in elderly people [10,11]. In a previous case-control study of factors associated with injurious falls we also found associations between psychoactive medication use and quadriceps strength, postural sway and two clinical balance measures: static and dynamic balance [12].…”
Section: Introductionmentioning
confidence: 59%
“…Following a single dose administration of loprazolam (0.5 mg and 1.0 mg) elderly and young adults did not differ significantly on Tmax nor on peak plasma concentrations of the drug, whereas T and area under the curve were significantly greater among the elderly, possibly reflecting slowing in drug metabolism and reduced hepatic clearance, or other age-related effects [60]. Residual effects (11 h after bedtime administration) for loprazolam 1.0 mg were significant on a standing steadiness test, but not on tests of critical flicker fusion nor on choice reaction time.…”
Section: Loprazolammentioning
confidence: 82%